Growth, size, ownership and control in the manufacturing sector of Petaling Jaya, 1971. - Asmah Ahmad (Universiti Kebangsaan Malaysia, 1976)
This paper tries to highlight two main characteristics of the manufacturing industry in Petaling Jaya. First, the growth of manufacturing, and secondly, the nature of the industrial investment found. An analysis of available statistics and information gathered from a survey carried out in 1974 shows that 1) the size of the establishments is large both in terms of its gross value of sales and employment size, 2) Malaysian owns a substantial percentage (38%) of the total establishment, and/but, 3) it is the foreign-owned firms that dominate a major portion of the value of sales and value added.